2010
DOI: 10.1186/1475-2875-9-262
|View full text |Cite
|
Sign up to set email alerts
|

Field experiments of Anopheles gambiae attraction to local fruits/seedpods and flowering plants in Mali to optimize strategies for malaria vector control in Africa using attractive toxic sugar bait methods

Abstract: BackgroundBased on recent studies in Israel demonstrating that attractive toxic sugar bait (ATSB) methods can be used to decimate local anopheline and culicine mosquito populations, an important consideration is whether the same methods can be adapted and improved to attract and kill malaria vectors in Africa. The ATSB approach uses fruit or flower scent as an attractant, sugar solution as a feeding stimulant, and an oral toxin. The ATSB solutions are either sprayed on vegetation or suspended in simple bait st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 21 publications
(30 reference statements)
2
97
0
Order By: Relevance
“…The low blood feeding response in late October-November coincides with the apparent disappearance of the M form (Adamou et al, 2011; Lehmann et al, 2010) from indoor collections. Presumably these mosquitoes fly to unknown shelters and feed on plants (Muller et al, 2010) as proposed by (Huestis et al, 2011). On the other hand, the relative scarcity of unfed females during the dry season suggests that those females which do enter houses are highly intent on blood feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The low blood feeding response in late October-November coincides with the apparent disappearance of the M form (Adamou et al, 2011; Lehmann et al, 2010) from indoor collections. Presumably these mosquitoes fly to unknown shelters and feed on plants (Muller et al, 2010) as proposed by (Huestis et al, 2011). On the other hand, the relative scarcity of unfed females during the dry season suggests that those females which do enter houses are highly intent on blood feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of guava fruit with CO 2 caught a smaller number of mosquitoes when compared to CO 2 alone. According to a study in Mali, guava fruit was the most attractive fruit for both female and male A.gambiaes [26]. The difference of guava fruits may be the possible reason for the unparalleled efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of sugar sources (e.g. Müller et al, 2010), blood and water (around houses and in wells) probably relaxes the constraints imposed by limited food and water typically available to diapausing insects. Consistent with this, we (Yaro et al, 2012) found that reproductive physiology, but not blood-feeding response, was depressed during the dry season in Sahelian M-form A. gambiae.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that these relatively small individuals surviving until the end of the dry season (April-May) have greater nutritional reserves (relative to their body size) than do mosquitoes at other times of the year. Considering the abundance of flowers and fruits during the dry season (Müller et al, 2010), continued availability of human hosts and the hospitable temperature range, mosquitoes may amass nutritional reserves until they can later allocate them to reproduction. It is possible that these seasonal shifts in body size are mostly due to the drying of larval sites at the end of the wet season, which in turn affects larval density and thus food availability and larval growth patterns, as it is well known that growing conditions affect adult size (Lanciani, 1992;Fischer and Fiedler, 2002;Chown and Klok, 2003;Aboagye-Antwi and Tripét, 2010;Russell et al, 2011).…”
Section: Discussionmentioning
confidence: 99%